2006
DOI: 10.1002/cphc.200500327
|View full text |Cite
|
Sign up to set email alerts
|

From Pentalene to Dicyclopenta[b,g]naphthalene, or the Change towards Delocalized Structures

Abstract: Using triples-corrected coupled-cluster methods as well as other high-level theoretical approximations, the optimized parameters and isomerization barriers of the family of compounds cyclopentadiene-(benzene)x-cyclopentadiene (x = 0, 1, 2) are computed. In contrast to previous studies, s-indacene presents a localized C(2h) geometry. Also, the localized structure of pentalene is found to be the most stable, but when two benzene rings are intercalated between the five-member rings of pentalene, the resulting mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, the previous studies only focus on the fine-tuning deformation of the host without noting that of guest. [33,47,48] The calculations here clearly revealed that the induced mutual-fit interaction not merely comes from the contribution of [6]CPPA host, but also that of C 70 guest. This simultaneously suggests that both [6] CPPA and C 70 are highly elastic molecules.…”
Section: Geometrics and Binding Energiesmentioning
confidence: 70%
See 3 more Smart Citations
“…However, the previous studies only focus on the fine-tuning deformation of the host without noting that of guest. [33,47,48] The calculations here clearly revealed that the induced mutual-fit interaction not merely comes from the contribution of [6]CPPA host, but also that of C 70 guest. This simultaneously suggests that both [6] CPPA and C 70 are highly elastic molecules.…”
Section: Geometrics and Binding Energiesmentioning
confidence: 70%
“…The calculated lengths of the long axis and short axis in the isolated [6]CPPA are 13.31 and 12.90 Å, respectively, in good agreement with ab initio results. [33,34] It can be seen from Table 1 that among all the configurations of the complexes, the two centers of the host and guest are not overlapping with the distances between two centers, d c-c , in the range of 1.0~2.8 Å. The d c-c in the two standing isomers are relative small and in the range of 1.0~1.1 Å, but these of lying and half-lying isomers are larger and in the range of 2.1~2.8 Å.…”
Section: Geometrics and Binding Energiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally and qualitatively speaking, if the frontier orbitals are obviously extended across the 2 or more fragments of a complex or a supramolecular system, charge transfer (CT) between the fragments is suggested; otherwise, CT can be excluded. [44] As shown in Figure 3, it is clear that the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the host-guest complexes are completely localized on the C 60 or C 70 guest but independent of T3 or P3 nanorings. Similar results without crossing the 2 moieties can be found for the other complexes (see Figure S1 and Figure S2 of the Supporting Information), indicating the lack of obvious CT between O 6 -corona [6]arene nanoring and fullerene.…”
Section: Frontier Orbital Features and Fluorescence Emission Spectrmentioning
confidence: 95%